2012
DOI: 10.3136/fstr.18.391
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Effects of Unripe Persimmon (Diospyros kaki L. cv. Hiratanenashi) Fruit and Its Component in Spontaneously Hypertensive Rats

Abstract: The feeding of unripe persimmon (PP) ('Hiratanenashi', pollination variant) and soluble tannin (PST), as its component, on blood pressure was examined in spontaneously hypertensive rats (SHR). Systolic blood pressure (SBP) was decreased by PP and PST administration for 2-3 days and increased after switching to the basal diet alone. Increases in serum nitric oxide level and liver NOS3 gene expression in SHR fed PP suggests that the induction of nitric oxide formation by PP administration might be involved in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…A study conducted to investigate the anti-inflammatory effect of Persimmon extract among Wistar rats induced with collagen-induced arthritis (CIA) by an intradermal injection of an emulsion of bovine type II collagen in complete Freund's adjuvant reported a significant reduction in the oedema volume and radiological alterations caused as a result of CIA in the bone, suggesting the anti-inflammatory activity of the Persimmon extract (Direito et al, 2019). The presence of tannins in the fruit pulp of Persimmon possesses hydroxyl radical scavenging antioxidant capacities, which has been found to be effectual in alleviating the incidence of stroke (Liu et al, 2012;Park et al, 2017). A study conducted to investigate the protective effect and antioxidant activity of the ethyl acetate fraction from DKL (EFDK) on H 2 O 2 -induced hippocampal HT22 cells and trimethyltin chloride (TMT)-induced mice reported high antioxidant activities and neuroprotective effects of EFDK on HT22 cells.…”
Section: Health Benefits and Medicinal Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted to investigate the anti-inflammatory effect of Persimmon extract among Wistar rats induced with collagen-induced arthritis (CIA) by an intradermal injection of an emulsion of bovine type II collagen in complete Freund's adjuvant reported a significant reduction in the oedema volume and radiological alterations caused as a result of CIA in the bone, suggesting the anti-inflammatory activity of the Persimmon extract (Direito et al, 2019). The presence of tannins in the fruit pulp of Persimmon possesses hydroxyl radical scavenging antioxidant capacities, which has been found to be effectual in alleviating the incidence of stroke (Liu et al, 2012;Park et al, 2017). A study conducted to investigate the protective effect and antioxidant activity of the ethyl acetate fraction from DKL (EFDK) on H 2 O 2 -induced hippocampal HT22 cells and trimethyltin chloride (TMT)-induced mice reported high antioxidant activities and neuroprotective effects of EFDK on HT22 cells.…”
Section: Health Benefits and Medicinal Propertiesmentioning
confidence: 99%
“…The presence of PA found abundantly in Persimmon peel has been reported to be efficacious in managing obesity (Kim et al , 2016) as well as diabetes mellitus (Izuchi et al , 2011). It has been demonstrated that Persimmon, when administrated to diabetic patients by fruit peel, reduced lipid peroxidation and the production of reactive oxygen species (Jiang et al , 2019); lowered the levels of serum glucose (Liu et al , 2012), serum triglycerides (Song et al , 2020) and glycosylated haemoglobin (HbA1c) (Gato et al , 2013). A study conducted to investigate the anti-inflammatory effect of Persimmon extract among Wistar rats induced with collagen-induced arthritis (CIA) by an intradermal injection of an emulsion of bovine type II collagen in complete Freund’s adjuvant reported a significant reduction in the oedema volume and radiological alterations caused as a result of CIA in the bone, suggesting the anti-inflammatory activity of the Persimmon extract (Direito et al , 2019).…”
Section: Health Benefits and Medicinal Propertiesmentioning
confidence: 99%
“…Condensed tannin has been shown to exhibit high antioxidant activity [ 5 , 6 ]. Previous studies demonstrated that tannin in persimmon reduced blood pressure [ 7 ], exhibited antibacterial activities [ 6 , 8 ], and exerted hypolipidemic effects [ 9 , 10 ]. Furthermore, persimmon was found to exert different beneficial effects against diseases, such as hypertension, diabetes mellitus, and atherosclerosis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…1) The fruit is highly nutritious, and contains various types of tannins, polyphenols, carotenoids, potassium, vitamins, and dietary fiber. 2,3) Several studies have demonstrated that consumption of persimmon helps to ameliorate various diseases, including cardiovascular disease, 4) diabetes, [5][6][7][8] obesity, [9][10][11][12][13][14] and hypertension. 15) Despite its health-promoting potential, persimmon has several properties that prevent its more widespread consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, fermented legumes have greater antioxidant activity than fresh legumes. 21,22) Although dietary supplementation with persimmon extracts can lower the plasma triglycerides (TGs) and cholesterol levels of laboratory animals with experimentally induced obesity, [9][10][11][12][13][14] the underlying mechanisms are yet to be elucidated. Moreover, the effects of fermented persimmon extracts (FPE) on the metabolic parameters and the underlying mechanisms of these effects are essentially unknown.…”
Section: Introductionmentioning
confidence: 99%